Harold Gatty papers - Gatty, Harold, 1903-1957.; Gatty, Harold, 1903-1957.; Gatty, Harold, 1903-1957.; Mills, Enos Abijah, 1870-1922.
Correspondence, writings, research notes, subject files, indexes, bibliographies, clippings, charts, maps, drawings, and other papers relating chiefly to the history of land and nautical navigation. Documents Gatty's investigations of air, water, and land navigation, particularly in Polynesia, the Arctic, and the Antarctic; his development of air routes for the South Seas Commercial Company founded by Gatty and Donald W. Douglas, Pan American Airways Corporation, and other transpacific flights; and Gatty's attempted transpacific flight with Harold Bromley in 1931. Includes drafts of Gatty's books Raft Book: Lore of the Sea & Sky (1943) and Nature Is Your Guide (1958) and a typescript of The Adventures of a Nature Guide by Enos Abijah Mills, published in 1920.
Smithsonian Institution.
Aviator, navigator, naturalist, and inventor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bromley, Harold, -- 1898-1998.; Douglas, Donald W. -- 1892-1981.; Pan American Airways Corporation; South Seas Commercial Company; Airways -- Pacific area; Navigation; Navigation -- Antarctica; Navigation -- Arctic regions; Navigation -- Polynesia; Navigation (Aeronautics); Transpacific flights; Aviators; Inventors; Naturalists; Navigators